2018
DOI: 10.1016/j.bpsc.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Mechanisms of Therapeutic Transcranial Magnetic Stimulation for Major Depressive Disorder

Abstract: Research into therapeutic transcranial magnetic stimulation (TMS) for major depression has dramatically increased in the last decade. Understanding the mechanism of action of TMS is crucial to improve efficacy and develop the next generation of therapeutic stimulation. Early imaging research provided initial data supportive of widely held assumptions about hypothesized inhibitory or excitatory consequences of stimulation. Early work also indicated that while TMS modulated brain activity under the stimulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 90 publications
7
59
0
Order By: Relevance
“…Firstly, identifying a core dysfunctional region in ASD bears direct implications to the development of novel therapeutic interventions. For example, in depression disorder, classical rest functional abnormalities in frontal regions have been the ground to development of transcranial magnetic stimulation (TMS) protocols applied to this region, with significant clinical improvements [40,41]. Results presented here suggest that STS could become an interesting target for this type of intervention in ASD.…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, identifying a core dysfunctional region in ASD bears direct implications to the development of novel therapeutic interventions. For example, in depression disorder, classical rest functional abnormalities in frontal regions have been the ground to development of transcranial magnetic stimulation (TMS) protocols applied to this region, with significant clinical improvements [40,41]. Results presented here suggest that STS could become an interesting target for this type of intervention in ASD.…”
Section: Discussionmentioning
confidence: 90%
“…Focal brain stimulation has been associated with changes that spread through the intrinsic networks of the brain and which outlast the actual stimulation period [17], including stimulation of the dorsolateral prefrontal cortex (DLPFC) which represents the primary and currently most effective target for non-invasive brain modulation in both MDD and GAD [18,19]. In line with these findings the anti-depressive treatment efficacy of non-invasive transcranial DLPFC stimulation has been associated with effects in distal brain regions and reorganization of multiple intrinsic brain networks, suggesting an important role of network level effects for therapeutic efficacy [20]. The most efficient stimulation targets across invasive and non-invasive targets are linked by shared intrinsic networks, further emphasizing the therapeutic and mechanistic importance of network level effects [21].…”
Section: Introductionmentioning
confidence: 97%
“…In PTSD+MDD, stronger amygdala‐to‐medial prefrontal cortex (MPFC) functional connectivity at baseline predicted superior improvement (Philip et al, ). Other studies have found predictive differences in pre‐TMS DLPFC‐striatum connectivity (Avissar et al, ; Kang et al, ), as well as between CEN and salience processing regions (Philip, Barredo, Aiken, & Carpenter, ).…”
Section: Introductionmentioning
confidence: 91%